Role of mesoscale eddies in the biogeochemistry of the Mozambique Channel - Chenillat, Fanny; Deshaies, Eloise; Arens, Aline; Penven, Pierrick (Frontiers in Marine Science, 2024)
This study aims to characterize how eddies shape the biogeochemistry of the Mozambique Channel using a physical-biogeochemical model that realistically simulates its interannual dynamics. The 20-year-long numerical simulation provides a comprehensive dataset for robust statistical analysis of thousands of mesoscale features using an eddy detection method. We show that all eddy types significantly shape the biogeochemical landscape over the Mozambique Channel, with varying effects across different areas: (1) Sofala Bank and Delagoa Bay: Cyclonic eddies enhance diatom production. (2) Comoros Basin: Cyclonic eddies favor diatom growth via nutrient-rich waters from the NEMC. (3) Central Mozambique Channel: Anticyclonic eddies and rings promote nanophytoplankton through eddy-topography interactions. (4) Southern Mozambique Channel: A mix of eddies from the MC and South Madagascar influences diverse responses due to coastal upwelling. This diversity of processes results in distinct biological signatures of eddy types, leading to diverse ecosystem assemblages with a clear oligotrophic signature.